Polymeric Nanoparticles with Sequential and Multiple FRET Cascade Mechanisms for Multicolor and Multiplexed Imaging. Issue 12 (29th January 2013) - Wagh, Anil; Jyoti, Faidat; Mallik, Sanku; Qian, Steven; Leclerc, Estelle; Law, Benedict
Abstract The ability to map multiple biomarkers at the same time has far‐reaching biomedical and diagnostic applications. Here, a series of biocompatible poly(d, l‐lactic‐co‐glycolic acid) and polyethylene glycol particles for multicolor and multiplexed imaging are reported. More than 30 particle formulations that exhibit distinct emission signatures (ranging from the visible to NIR wavelength region) are designed and synthesized. These particles are encapsulated with combinations of carbocyanine‐based fluorophores DiO, Dil, DiD, and DiR, and are characterized as <100 nm in size and brighter than commercial quantum dots. A particle formulation is identified that simultaneously emits fluorescence at three different wavelengths upon a single excitation at 485 nm via sequential and multiple FRET cascade events for multicolor imaging. Three other particles that display maximum fluorescence intensities at 570, 672, or 777 nm for multiplexed imaging are also identified. These particles are individually conjugated with specific (Herceptin or IgG2A11 antibody) or nonspecific (heptaarginine) ligands for targeting and, thus, could be applied to differentiate different cancer cells from a cell mixture according to the expressions of cell‐surface human epidermal growth factor receptor 2 and the receptor for advanced glycation endproducts. Using an animal model subcutaneously implanted with the particles, it is further demonstrated that the developed platform could be useful for in vivo multiplexed imaging.